Fructosamine and HbA1c: A Correlational Study in a Southeast Asian Population - Chandran, Kurumbian; Lee, See Muah; Shen, Liang; Tng, Eng Loon (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. Fructosamine correlates well with glycated haemoglobin (HbA1c) in Caucasians. This study investigates this correlation and whether fructosamine can reliably estimate glycated haemoglobin in Southeast Asians. Methodology. We recruited 193 participants based on 4 HbA1c bands (<6.0%; 6.0 – 7.9%; 8.0– 9.9%; ≥10%) from a secondary hospital in Singapore between August 2017 and December 2021. Blood samples for fructosamine, glycated haemoglobin, albumin, haemoglobin, thyroid stimulating hormone and creatinine were drawn in a single setting for all participants. Scatter plot was used to explore correlation between fructosamine and glycated haemoglobin. Strength of linear correlation was reported using Pearson’s correlation coefficient. Simple linear regression was used to examine the relationship between fructosamine and glycated haemoglobin. Results. We performed simple linear regression to study the relationship between fructosamine and HbA1c in the research participants (R2 = 0.756, p<0.01). Further analysis with natural logarithmic transformation of fructosamine demonstrated a stronger correlation between HbA1c and fructosamine (R2 = 0.792, p<0.01). Conclusions. Fructosamine is reliably correlated with HbA1c for the monitoring of glycaemic control in Southeast Asians.